Benefits of treatment with implantable cardioverter-defibrillators in patients with stable ventricular tachycardia without cardiac arrest. Issue 2 (February 1995) - Böcker, D.; Block, M.; Isbruch, F.; Fastenrath, C.; Castrucci, M.; Hammel, D.; Scheld, H. H.; Borggrefe, M.; Breithardt, G.
Abstract : BACKGROUND–The availability of implantable cardioverter-defibrillators (ICD) that are capable of antitachycardia pacing may lead to an increased use of ICDs in patients with haemodynamically tolerated ventricular tachycardia without a history of cardiac arrest. The frequency of potentially life-threatening fast ventricular tachycardias (cycle length < 250 ms) was investigated in patients who had a third generation ICD with endocardial leads implanted because they had haemodynamically tolerated ventricular tachycardia without a history of cardiac arrest. METHODS–Between January 1990 and October 1993, 50 patients (age (mean (SD)) 60 (11); ejection fraction 39 (16)%; 82% with coronary artery disease and 8% with dilated cardiomyopathy) with haemodynamically tolerated ventricular tachycardia (cycle length (mean (SD)) 348 (60) ms; range 250-500 ms) and without a history of cardiac arrest were treated with third generation ICDs that were capable of antitachycardia pacing. Fast ventricular tachycardia had been induced in 14 (28%) during baseline electrophysiological study. The benefit of ICD treatment was estimated as the difference between total mortality and the occurrence of fast ventricular tachycardia that would have been fatal if it had not been terminated. RESULTS–During follow up of 17 (12) months, 33 patients (66%) had a total of 3861 episodes of ventricular tachycardia. 91% of these episodes were terminated by antitachycardia pacing. 11 patients (22%) had episodes of potentially life-threatening fast ventricular tachycardia and 3 of these also had inducible fast ventricular tachycardia. One patient died suddenly 27 months after implantation. The difference between survival without fast ventricular tachycardia and total mortality was 9%, 12%, 27%, and 27% at 6, 12, 18, and 24 months, respectively. CONCLUSIONS–About a fifth of patients who had been given an ICD to treat haemodynamically tolerated ventricular tachycardia and who had no history of cardiac arrest experienced fast ventricular tachycardia during follow up requiring immediate cardioversion. Prospective studies are needed to investigate whether the prognosis of patients with a history of haemodynamically tolerated ventricular tachycardia without cardiac arrest is improved by ICD therapy.